KASAMBANG VILLAGE, MAMUJU DISTRICT: DEVELOPMENT OF PIKO HYDRO POWER PLANT USING FLOW RICE IRRIGATION IN KASAMBANG VILLAGE - Yusuf Mappeasse, Muhammad; Haripuddin, Haripuddin; Zauqi, Andi (Journal of Electrical Engineering and Informatics, 2023)
Pico Hydro Power Plant (PLTPH) is one of the power plants that uses water as an energy source. Piko Hydro is included in the category of hydropower plants with small power because it does not need to use a water discharge that is too large to produce power. The tool developed in this study is a Pico Hydro Power Plant by Utilizing Flow Irrigation. The purpose of this research is to find out the results of the development of a Pico Hydro Power Plant, the electrical energy produced, and the community's response. The research method used is descriptive-quantitative with Research and Development (R&D) research and a prototype development model consisting of 4 steps, namely needs analysis, building prototypes, installing, and evaluating. The research data obtained by observation, questionnaires, and documentation. The results showed that the pico-hydro power plant works well, as indicated by the very good product validation value; the water wheel at the generator has a maximum power of 308 watts; and in development with the application of MPPT type charger control regulators, the results are able to stabilize the electrical energy produced and increase the power capability of the power plant with the help of a backup battery supply. For the results of the responses from the Kasambang Village community in Mamuju Regency, as many as 15 respondents obtained very decent results.